Diisocyanate-based free radical polymerizable silane coupling compound having urethane bonds

The novel silane coupling agent addresses mechanical strength and durability issues in dental composite resins by providing high affinity to radical polymerizable monomers, enhancing mechanical properties and color stability without hydrosilylation, using aliphatic diisocyanates and cyclic compounds for improved solubility.

CN112771057BActive Publication Date: 2024-12-20SHOFU INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980062417.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-28
Filing Date
2019-09-25
Publication Date
2024-12-20
Estimated Expiration
2039-09-25

AI Technical Summary

Technical Problem

Existing dental composite resins face issues with insufficient mechanical strength, durability, and water resistance due to the limitations of current silane coupling agents, and the use of hydrosilylation reactions leads to the need for expensive noble metal catalysts and potential yellowing of the cured product.

Method used

A novel silane coupling agent with a chemical structure that imparts high affinity to radical polymerizable monomers, enhancing mechanical strength and durability, and is synthesized without hydrosilylation, using aliphatic diisocyanates and cyclic compounds as reaction substrates, allowing for improved solubility in organic solvents like toluene.

Benefits of technology

The novel silane coupling agent achieves high mechanical strength, durability, and color stability by forming carbamate bonds, improving the adhesion and filling rate of inorganic fillers in dental compositions, while avoiding the use of noble metal catalysts and their yellowing effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDF0000034567050000011
    Figure FDF0000034567050000011
  • Figure FDF0000034567050000021
    Figure FDF0000034567050000021
  • Figure FDF0000034567050000022
    Figure FDF0000034567050000022
Patent Text Reader

Abstract

The present invention relates to a novel free radical polymerizable silane coupling compound having a urethane bond based on a diisocyanate and a medical and dental curable composition containing the same. The present invention provides a novel silane coupling agent which imparts high affinity to a free radical polymerizable monomer having a urethane group and thus imparts high mechanical strength and durability when used in a medical and dental curable composition, an inorganic filler surface-treated with the novel silane coupling agent, and a novel medical and dental curable composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to novel free radical polymerizable silane coupling compounds having urethane bonds based on diisocyanate and to medical and dental curable compositions containing the same. Background Art

[0002] In the field of medical dentistry, in order to repair the defect of bone and tooth, metal restorations, synthetic resin moldings, etc. can be used. In order to bond with these biological hard tissues, adhesives containing bonding polymerizable monomers are mostly used. In addition, in the field of dentistry, medical dentistry curable compositions referred to as so-called composite resins are used every day in the clinic. It is by filling uncured body (before free radical polymerization) paste into the defective part of tooth, etc., then, giving external energy such as light irradiation, thereby obtaining free radical polymerization cured body.

[0003] Generally speaking, (meth) acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and carbamate dimethacrylate are used in these adhesives and composite resins. In the free radical polymerization (hereinafter referred to as free radical polymerization) of vinyl monomers such as these (meth) acrylic acid derivative monomers, the carbon-carbon double bond is broken into a single bond, thereby forming a polymer and curing. In addition to the vinyl monomer, in order to improve the mechanical strength, an inorganic filler is also added to the composite resin. Generally speaking, these inorganic fillers are surface treated with a silane coupling agent having a polymerizable group to achieve improved wettability and improved mechanical strength. In the dental field, γ-methacryloxypropyltrimethoxysilane (hereinafter referred to as KBM-503) has been widely used as a silane coupling agent. When using particles treated with the surface of the compound, there is a problem that the hydrophobicity is low and the hydrolysis is easy, and the durability of the material is low. In addition, there is also a disadvantage that the filling rate of the inorganic filler is low due to its low hydrophobicity, and sufficient mechanical strength cannot be obtained.

[0004] When the basic skeleton of the (meth)acrylic acid derivative monomer used in the composite resin is an ethylene glycol chain or an alkylene chain, a silane coupling agent such as KBM-503 can also improve wettability and mechanical strength to some extent.

[0005] Therefore, in order to improve the durability and filling rate of the material, the following methods have been proposed: using a silane coupling agent with a longer alkyl chain (Patent Documents 1, 2, 3); using a silane coupling agent with a fluoroalkylene group (Patent Document 4); and using a silane coupling agent with a large number of polymerizable groups (Patent Document 5).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2-134307

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 3-70778

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 2015-196682

[0011] Patent Document 4: Japanese Patent Application Laid-Open No. 2007-238567

[0012] Patent Document 5: Japanese Patent Application Laid-Open No. 2010-229054 Summary of the invention

[0013] Problem that the invention aims to solve

[0014] When the methods described in Patent Documents 1 to 3 are applied to dental composite resins, which are one of the dental curable compositions, there is room for improvement in terms of mechanical strength. In addition, when the method described in Patent Document 4 is applied to dental materials, the water resistance is low and the durability of the material is insufficient. Thus, the durability and mechanical strength of the materials using silane coupling agents in the prior art are not sufficiently balanced, and there is room for further improvement.

[0015] In addition, in the existing method of using hydrosilylation reaction when synthesizing silane coupling agents, expensive noble metal catalysts such as platinum and palladium are required, and sometimes the yellowing of the cured body is caused by the residue of the noble metal catalyst. As a synthesis method without using the hydrosilylation reaction, there is also the following synthesis method: by reacting an isocyanate group with a compound having hydroxyl groups at both ends, a free radical polymerizable group and an alkoxysilane group are introduced into one molecule. For example, a silane coupling agent can be synthesized by reacting decane-1,10-diol, 2-isocyanateethyl methacrylate and (3-isocyanatepropyl)trimethoxysilane in a tetrahydrofuran solvent. However, the good solvents for compounds such as alkyl glycols and polyethylene glycols are only hydrophilic low-boiling point compounds such as acetone and tetrahydrofuran, and are not soluble in hydrophobic high-boiling point solvents such as toluene. Therefore, water dissolved in acetone, tetrahydrofuran, etc. must be removed before use. In addition, due to the low boiling point, the carbamate reaction of the isocyanate group and the hydroxyl group takes a long time. In addition, when the molecular weight of diol or the like increases, the melting point becomes higher than room temperature, and a pure (solvent-free) reaction becomes difficult.

[0016] The present invention aims to provide a novel silane coupling agent that imparts high affinity to a radical polymerizable monomer having a carbamate group, thereby imparting high mechanical strength and durability when used in a medical and dental curable composition, an inorganic filler surface-treated with the novel silane coupling agent, and a novel medical and dental curable composition. Furthermore, the present invention aims to provide a cured product having excellent color stability by not using a hydrosilylation reaction when synthesizing the silane coupling agent and not causing yellowing of the cured product due to residual noble metal catalysts.

[0017] Solutions for solving problems

[0018] The present inventors have conducted intensive research and found that the inorganic filler can be surface treated with a silane coupling agent represented by the following chemical formula to impart high affinity to the radical polymerizable monomer, thereby imparting high mechanical strength when used in a medical and dental curable composition.

[0019] [Chemical formula 1]

[0020]

[0021] In the above chemical formula,

[0022] A represents a H2C=CH-, H2C=C(CH3)- or H2C=CH-C6H4- group (C6H4 represents a phenylene group); B represents a -C(O)-O-, -C(O)-S-, -C(O)-NH-, -NH-C(O)-NH-, -NH-C(O)-S- or -NH-C(O)-O- group; R 1 is a C2-C100 straight-chain or branched alkylene group, which may contain one or more of -O-CH2-CH2-, -O-CH(CH3)-CH2- and -CH(CH3)-CH2-O- groups; Z contains at least one benzene ring or cyclohexane ring, and / or a C2-C100 straight-chain or branched alkylene group; R 2 represents a C2-C100 straight-chain or branched alkylene group; R 3 represents a C1-C6 straight-chain or branched alkyl group; R 4 represents a C1-C16 straight-chain or branched alkyl group, a phenyl group or a halogen atom, and when n is 0, at least one halogen atom is bonded to Si. In addition, a is 1-6, and n is 0-3.

[0023] Effects of the Invention

[0024] By treating the inorganic filler with the silane coupling agent of the present invention, a high affinity for the radical polymerizable monomer is exhibited, and as a result, a high mechanical strength, softness (pliability) and adhesiveness and close adhesion are imparted to the medical and dental curable composition. In addition, no hydrosilylation reaction is used when synthesizing the silane coupling agent, and yellowing of the cured product due to the residual noble metal catalyst does not occur, so the color stability of the cured product is excellent.

[0025] This high affinity effect is significantly manifested when the radical polymerizable monomer has a carbamate group. It is believed that the reason is that there are two carbamate bonds in the formula [Chemical Formula 1]. That is, it is believed that the inorganic filler surface-treated with the silane coupling agent of the present invention has a carbamate group introduced on its surface, and the carbamate group significantly manifests a high affinity for the radical polymerizable monomer having a carbamate group. According to the present invention, high filling of the inorganic filler becomes possible, and as a result, high mechanical strength can be achieved.

[0026] In addition, the silane coupling compound of the present invention uses aliphatic diisocyanates and / or diisocyanates with cyclic compounds as skeletons as reaction substrates, and their good solvents are toluene and the like. Therefore, compared with compounds with poor solubility in organic solvents such as 1-10-decanediol, the number of organic solvents that can be selected is increased, and a higher temperature can be selected in the urethane reaction. DETAILED DESCRIPTION

[0027] The molecular structure of the silane coupling agent having a radical polymerizable group in the present invention is a structure represented by [Chemical Formula 2], and one or more of them can be used in combination.

[0028] If the structure shown in [Chemical Formula 2] is described in more detail, A represents H2C=CH-, H2C=C(CH3)- or H2C=CH-C6H4- group (C6H4 represents phenylene group); B represents -C(O)-O-, -C(O)-S-, -C(O)-NH-, -NH-C(O)-NH-, -NH-C(O)-S- or -NH-C(O)-O- group; R 1is a C2-C100 (preferably C2-C40, more preferably C2-C25, and further preferably C2-C12) linear or branched alkylene group, and may contain one or more of -O-CH2-CH2-, -O-CH(CH3)-CH2-, and -CH(CH3)-CH2-O- groups; Z contains at least one benzene ring or cyclohexane ring, and / or a C2-C100 (preferably C2-C40, more preferably C2-C25, and further preferably C2-C12) linear or branched alkylene group or is composed of at least one benzene ring or cyclohexane ring, and / or a C2-C100 (preferably C2-C40, more preferably C2-C25, and further preferably C2-C12) linear or branched alkylene group; R 2 represents a C2-C100 straight-chain or branched alkylene group; R 3 represents a C1-C6 straight-chain or branched alkyl group; R 4 represents a C1-C16 straight-chain or branched alkyl group, a phenyl group or a halogen atom, and when n is 0, at least one halogen atom is bonded to Si. In addition, a is 1-6, and n is 0-3.

[0029] [Chemical formula 2]

[0030]

[0031] In addition, when the inorganic filler is surface treated with the silane coupling agent of the present invention, the treatment concentration also depends on the silanol group density (mol / g) of the mother particle, but is generally preferably 0.05 to 10 times by mass of the inorganic filler. In the treatment of less than 0.05 times by mass, the silane coupling agent cannot be fully introduced, and in the case of exceeding 10 times by mass, only condensation products of the silane coupling agent are generated, which affects the mechanical strength, so it is not preferred.

[0032] The chemical structures of representative compounds of the silane coupling compound of the present invention are described below.

[0033] [Chemical formula 3]

[0034]

[0035] [Chemical formula 4]

[0036]

[0037] [Chemical formula 5]

[0038]

[0039] As the inorganic filler treated with the silane coupling agent of the present invention, their chemical composition is not particularly limited, and examples thereof include silica, alumina, silica-titania, silica-titania-barium oxide, silica-zirconium oxide, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramics, aluminum silicate glass, barium borosilicate glass, strontium borosilicate glass, aluminum fluorosilicate glass, calcium aluminum fluorosilicate glass, strontium aluminum fluorosilicate glass, barium aluminum fluorosilicate glass, strontium calcium aluminum fluorosilicate glass, etc. In particular, barium aluminum fluorosilicate glass, strontium aluminum fluorosilicate glass, aluminum fluorosilicate glass, etc. used in dental glass ionomer cements, resin-reinforced glass ionomer cements, and resin cements can also be suitably used. The aluminum fluorosilicate glass referred to here refers to a glass having silicon oxide and aluminum oxide as a basic skeleton and containing an alkali metal for introducing non-crosslinking oxygen. It further has an alkaline earth metal containing strontium and fluorine as a modified and coordinated ion. In addition, in order to further impart X-ray opacity, it is a composition in which a lanthanum series element is doped into the skeleton. The lanthanum series element also participates in the composition as a modified and coordinated ion according to the composition domain. They can be used alone or in a mixture of two or more. The composition ratio of the inorganic filler treated with the silane coupling agent of the present invention in the medical and dental curable composition of the present invention is not particularly limited, and is preferably in the range of 25 to 90 weight %. When it is less than 25 weight %, the mechanical (physical) strength of the cured product is low, so it is not preferred. In addition, when it is more than 90 weight %, the viscosity of the prepared paste is too high, so it is not preferred because of poor clinical operability. Furthermore, the average particle size of the aforementioned inorganic filler is preferably 0.001 to 100 μm, and more preferably 0.001 to 10 μm. Furthermore, the shape of the inorganic filler can be spherical or indefinite. In this specification, the "average particle size" refers to a particle size at a cumulative value of 50% in a particle size distribution determined by a laser diffraction / scattering method.

[0040] When the silane coupling agent of the present invention is used in a curable composition for medical dentistry, the radical polymerizable monomer contained in the curable composition for medical dentistry is preferably contained in an amount of 10 to 60% by weight, more preferably 15 to 30% by weight. If it is less than 10% by weight, the viscosity of the curable composition for medical dentistry is too high, which may cause a problem, and if it is more than 60% by weight, the strength of the curable composition for medical dentistry may be reduced.

[0041] The free radical polymerizable monomer used in the medical dental curable composition of the present invention can use any substance used in the dental field without any limitation, but preferably has a carbamate bond in its molecular skeleton. Further, it can have a benzene ring and / or a cyclohexane ring in its molecular skeleton. This is because the carbamate bond (-NH-C(O)-O-) effectively forms a hydrogen bond with the silane coupling agent of the present invention. Examples of the free radical polymerizable monomers in the present invention include: 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl dimethacrylate (UDMA) synthesized by the carbamate reaction of 2,2,4-trimethylhexamethylene diisocyanate and 2-hydroxyethyl methacrylate (HEMA); free radical polymerizable monomers synthesized by the carbamate reaction of HEMA, hydroxyethyl acrylate (HEA) and 2,4-toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate or hexamethylene diisocyanate; carbamate diacrylates obtained by the reaction of aliphatic and / or aromatic diisocyanates with (meth) glycerol acrylate and 3-methacryloyl-2-hydroxypropyl ester; carbamate reaction products of 1,3-bis(2-isocyanate, 2-propyl)benzene and a compound having a hydroxyl group, etc. More specifically, 2,7,7,9,15-pentamethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 2,7,7,9,15-pentamethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaeicos-19-enyl methacrylate, 2,8,10,10,15-pentamethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaeicos-19-enyl methacrylate, 2,7,7,9,15-pentamethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, bis(oxymethylene)bis(propane-2,1-diyl) diacrylate, 2-((2-(((1-(acryloyloxy)propane-2-yloxy)carbonylamino)methyl)cyclohexyl)methylcarbamoyloxy)propyl methacrylate, 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methacrylate), 2,2'-(bicyclo[4.1.0]heptane-3,4-diylbis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl)diacrylate1-diyl) diacrylate, 2-((4-(((1-(acryloyloxy)propane-2-yloxy)carbonylamino)methyl)bicyclo[4.1.0]heptane-3-yl)methylcarbamoyloxy)propyl methacrylate, 2,2'-(bicyclo[4.1.0]heptane-3,4-diylbis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methylacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 7,7,9-trimethyl-4,13,18-trioxo-3,14,17-trioxa-5,12- Diazaicosa-19-enyl methacrylate, 8,10,10-trimethyl-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaicosa-19-enyl methacrylate, 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methacrylate), 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl diacrylate, 4,13,18-trioxo-3,14,17-trioxa-5,12-diazaicosa-19-enyl methacrylate, 4,13-dioxo-3,14-dioxa -5,12-diazahexadecane-1,16-diylbis(2-methacrylate), 2-(1-(2-((2-(acryloyloxy)ethoxy)carbonylamino)-4,4-dimethylcyclohexyl)ethylcarbamoyloxy)ethyl methacrylate, 2-(1-(2-((2-(acryloyloxy)ethoxy)carbonylamino)ethyl)-5,5-dimethylcyclohexylcarbamoyloxy)ethyl methacrylate, 2-(2-(((1-(methacryloyloxy)propane-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diylbis(2-methacrylate), 2-(2-(((1-(methacryloyloxy)propane- 2-(((1-(acryloyloxy)propane-2-yloxy)carbonylamino)methyl)-2,5,5-trimethylcyclohexylcarbamoyloxy)propane-1,3-diylbis(2-methylacrylate), 3-(15-(2-(acryloyloxy)ethyl)-3,12,19-trioxo-2,13,18-trioxa-4,11-diazaheneicos-20-enyl)pentane-1,5-diyldiacrylate, 3-(15-(2-(acryloyloxy)ethyl)-3,12,19-trioxo-2,13,18-trioxa-4,11-diazaheneicos-20-enyl)pentane-1,5-diyldiacrylate,11-diazahenedec-20-enyl)pentane-1,5-diyl bis(2-methylacrylate), 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl) diacrylate, 2-((2-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)cyclohexyl)methylcarbamoyloxy)ethyl methacrylate, 2,2'-(cyclohexane-1,2-diylbis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl) bis(2-methylacrylate), 2,15-bis(cyclohexyloxymethyl)-4,13-dioxo-3,14-diyl 2,15-bis(cyclohexyloxymethyl)-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyl bis(2-methylacrylate), 2,15-bis(cyclohexyloxymethyl)-4,13,18-trioxo-3,14,17-trioxa-5,12-diazaeicos-19-enyl methacrylate, 1,18-bis(cyclohexyloxy)-5,14-dioxo-4,15-dioxa-6,13-diazaoctadecane-2,17-diyl diacrylate, 1-(cyclohexyloxy)-17-(cyclohexyloxymethyl)-5,14,19-trioxo-4, 15,18-trioxa-6,13-diazaheneicos-20-en-2-yl methacrylate, 1,18-bis(cyclohexyloxy)-5,14-dioxo-4,15-dioxa-6,13-diazaoctadecane-2,17-diylbis(2-methacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diylbis(2-methacrylate), 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diyldiacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene) )bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl) diacrylate, 2-(3-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)benzylcarbamoyloxy)ethyl methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(methylazanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(methylazanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate),1-diyl) diacrylate, 2-((3-((((2-(acryloyloxy)ethoxy)carbonyl)(methyl)amino)methyl)benzyl)(methyl)carbamoyloxy)ethyl methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl) diacrylate, 2-(3-(((2-(acryloyloxy)ethoxy)carbonylamino)methyl)benzylcarbamoyloxy)propylmethylacrylate 2-(3-(((1-(acryloyloxy)propane-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)ethyl methacrylate, 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(4,1-phenylene)bis(2-methacrylate), 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(4,1-phenylene)diacrylate, 4-(3-(((4-(acryloyloxy)phenoxy)carbonylamino)methyl)benzylcarbamoyloxy)phenyl methacrylate, 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(4,1-phenylene) bis(2-methacrylate), 4,4'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(butane-4,1-diyl) diacrylate, 4-(3-(((4-(acryloyloxy)butoxy)carbonylamino)methyl)benzylcarbamoyloxy)butyl methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methacrylate), 2-(3-(((1-(acryloyloxy)-3-phenoxypropane-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-phenoxypropyl methacrylate, 2-2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)bis(2-methacrylate), 2-2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl)bis(2-methacrylate), 2-2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl) diacrylate, 2-(3-(((1-(acryloyloxy)-3-(phenylamino)propane-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(phenylamino)propyl methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl) diacrylate, 2-(3-(((1-(acryloyloxy)-3-(phenylthio)propane- 2-(((1-(acryloyloxy)-3-(benzyloxy)propane-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(phenylthio)propyl methacrylate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(benzyloxy)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(benzyloxy)propane-2,1-diyl)diacrylate, 2-(3-(((1-(acryloyloxy)-3-(benzyloxy)propane-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(benzyloxy)propyl methacrylate, 2,2 '-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(methacryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(acryloyloxy)propane-2,1-diyl)dibenzoate, 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(1,3-phenylenebis(methylene))bis(azanediyl)bis(oxymethylene)bis( 2-(3-(((1-(acryloyloxy)-3-(2-phenylacetoxy)propane-2-yloxy)carbonylamino)methyl)benzylcarbamoyloxy)-3-(2-phenylacetoxy)propyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate),1-diyl) diacrylate, 2-(2-(3-(2-((2-(acryloyloxy)ethoxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)ethyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(methylazanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(methylazanediyl)bis(oxymethylene)bis(oxy)bis(ethane-2,1-diyl) diacrylate, 2-((2-(3-(2-(((2-(acryloyloxy)ethoxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)ethyl methacrylate, bis(propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((2-(acryloyloxy)ethoxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyl 2-(2-(3-(2-((1-(acryloyloxy)propane-2-yloxy)carbonylamino)propane-2-ylcarbamoyloxy)ethyl methacrylate, 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(4,1-phenylene)bis(2-methacrylate), 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(4,1-phenylene)diacrylate, 4-(2-(3-(2-((4-(acryloyloxy)phenoxy)carbonylamino)propane-2-ylcarbamoyloxy)ethyl methacrylate, )phenyl)propane-2-ylcarbamoyloxy)phenyl methacrylate, 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(butane-4,1-diyl)bis(2-methacrylate), 4,4'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(butane-4,1-diyl)diacrylate, 4-(2-(3-(2-((4-acryloyloxy)butoxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)butyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(butane-4,1-diyl)bis(3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-phenoxypropane-2-yloxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)-3-phenoxypropyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-phenoxypropane-2,1-diyl) diacrylate bis(2-methylacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(phenylamino)propane-2-yloxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)-3-(phenylamino)propyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylamino)propane-2,1-diyl) diacrylate bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl)bis(2-methacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl) diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(phenylthio)propane-2-yloxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)-3-(phenylthio)propyl methacrylate, 2-2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(phenylthio)propane-2,1-diyl) diacrylate bis(benzyloxy)propane-2,1-diyl)bis(2-methylacrylate), 2-(2-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(3-(benzyloxy)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(benzyloxy)propane-2-yloxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)-3-(benzyloxy)propyl methacrylate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(3-(benzyloxy)propane-2,1-diyl)diacrylatebis(2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(methacryloyloxy)propane-2,1-diyl) dibenzoate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(acryloyloxy)propane-2,1-diyl) dibenzoate, 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(2-phenylacetoxy) )propane-2,1-diyl)bis(2-methylacrylate), 2,2'-(2,2'-(1,3-phenylene)bis(propane-2,2-diyl))bis(azanediyl)bis(oxymethylene)bis(oxy)bis(3-(2-phenylacetoxy)propane-2,1-diyl)diacrylate, 2-(2-(3-(2-((1-(acryloyloxy)-3-(2-phenylacetoxy)propane-2-yloxy)carbonylamino)propane-2-yl)phenyl)propane-2-ylcarbamoyloxy)-3-(2-phenylacetoxy)propyl methacrylate, etc.

[0042] Preferably, the bis((((propane-2,2-diylbis(4,1-phenylene))bis(azanediyl))bis(carbonyl))bis(oxy))bis(ethane-2,1-diyl)bis(2-methylacrylate), ((((methylenebis(4,1-phenylene))bis(azanediyl))bis(carbonyl))bis(oxy))bis(ethane-2,1-diyl)bis(2-methylacrylate), ((((2-methyl-1,3-phenylene)bis(azanediyl))bis(carbonyl))bis(oxy))bis(ethane-2,1-diyl)bis(2-methylacrylate), ((((cyclohexane-1,3-diylbis(methylene))bis(azanediyl))bis(carbonyl) The invention is composed of a radical polymerizable monomer having a benzene ring and / or cyclohexane ring and a carbamate bond in the molecular skeleton, such as ((((methylenebis(4,1-phenylene))bis(azanediyl))bis(carbonyl))bis(oxy))bis(ethane-2,1-diyl) diacrylate, ((((2-methyl-1,3-phenylene)bis(azanediyl))bis(carbonyl))bis(oxy))bis(ethane-2,1-diyl) diacrylate, and ((((cyclohexane-1,3-diylbis(methylene))bis(azanediyl))bis(carbonyl))bis(oxy))bis(ethane-2,1-diyl)bis(2-methylacrylate).

[0043] [Chemical formula 6]

[0044]

[0045] [Chemical formula 7]

[0046]

[0047] When the silane coupling agent of the present invention is used in a medical and dental curable composition, it is preferred to contain at least one of a polymerization initiator or a polymerization accelerator. In addition, for its preferred blending amount, the blending amount of the polymerization initiator and the polymerization accelerator is preferably 0.5wt% to 5wt% relative to the free radical polymerizable monomer. This is because, when the concentration is lower than 0.5wt%, the unpolymerized free radical polymerizable monomer becomes more, so the mechanical strength decreases. In addition, when the concentration is higher than 5wt%, the degree of polymerization decreases and the mechanical strength decreases.

[0048] As the polymerization initiator contained in the medical dental curable composition of the present invention, it can be selected from the polymerization initiators used in the industry and used, wherein the polymerization initiator used in dental applications is preferably used. In particular, a polymerization initiator for photopolymerization and chemical polymerization is used alone or in a suitable combination of two or more. Specifically, as the photopolymerization initiator in the polymerization initiator contained in the medical dental curable composition of the present invention, (bis) acylphosphine oxides, water-soluble acylphosphine oxides, thioxanthones or quaternary ammonium salts of thioxanthones, ketals, α-diketones, coumarins, anthraquinones, benzoin alkyl ether compounds, α-aminoketone compounds, etc. can be cited.

[0049] Specific examples of the acylphosphine oxides used as the photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, 2,6-dichlorobenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylmethoxyphenylphosphine oxide, 2,4,6-trimethylbenzoylethoxyphenylphosphine oxide, 2,3,5,6-tetramethylbenzoyldiphenylphosphine oxide, and benzoylbis-(2,6-dimethylphenyl)phosphonate. Examples of the bisacylphosphine oxides include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide, bis-(2,6-dimethoxybenzoyl)phenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and (2,5,6-trimethylbenzoyl)-2,4,4-trimethylpentylphosphine oxide.

[0050] If the thioxanthones or quaternary ammonium salts of thioxanthones used as photopolymerization initiators are specifically exemplified, for example, thioxanthones, 2-chlorothioxanthen-9-one, 2-hydroxy-3-(9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-propane ammonium chloride, 2-hydroxy-3-(1-methyl-9-oxo-9H-thioxanthen-4-yloxy)-N,N,N-trimethyl-propane ammonium chloride, 2-hydroxy-3-(9-oxo-9H-thioxanthen-2-yloxy)-N, N,N-trimethyl-propane ammonium chloride, 2-hydroxy-3-(3,4-dimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, 2-hydroxy-3-(3,4-dimethyl-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, 2-hydroxy-3-(1,3,4-trimethyl-9-oxo-9H-thioxanthen-2-yloxy)-N,N,N-trimethyl-1-propane ammonium chloride, etc.

[0051] Specific examples of α-diketones used as the photopolymerization initiator include diacetyl, dibenzoin, camphorquinone, 2,3-pentanedione, 2,3-octanedione, 9,10-phenanthrenequinone, 4,4′-oxybenzyl, and acenaphthenequinone.

[0052] Specific examples of coumarin compounds used as photopolymerization initiators include 3,3'-carbonylbis(7-diethylaminocoumarin), 3-(4-methoxybenzoyl)coumarin, 3-thienoylcoumarin, 3-benzoyl-5,7-dimethoxycoumarin, 3-benzoyl-7-methoxycoumarin, 3-benzoyl-6-methoxycoumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoylcoumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3-benzoyl-8-methoxycoumarin, 3,5-carbonylbis(7-methoxycoumarin), 3 -Benzoyl-6-bromocoumarin, 3,3'-carbonylbiscoumarin, 3-benzoyl-7-dimethylaminocoumarin, 3-benzoylbenzo[f]coumarin, 3-carboxycoumarin, 3-carboxy-7-methoxycoumarin, 3-ethoxycarbonyl-6-methoxycoumarin, 3-ethoxycarbonyl-8-methoxycoumarin, 3-acetylbenzo[f]coumarin, 7-methoxy-3-(p-nitrobenzoyl)coumarin, 3-(p-nitrobenzoyl)coumarin, 3-benzoyl-8-methoxycoumarin, 3-benzoyl-6-nitrocoumarin, 3-benzoyl-7-diethylaminocoumarin, 7-dimethylamino-3-(4-methoxybenzoyl)coumarin, 7-diethylamino-3- (4-methoxybenzoyl) coumarin, 7-diethylamino-3-(4-diethylamino) coumarin, 7-methoxy-3-(4-methoxybenzoyl) coumarin, 3-(4-nitrobenzoyl)benzo[f]coumarin, 3-(4-ethoxycinnamoyl)-7-methoxycoumarin, 3-(4-dimethylaminocinnamoyl) coumarin, 3-(4-diphenylaminocinnamoyl) coumarin, 3-[(3-dimethylbenzothiazol-2-ylidene)acetyl]coumarin, 3-[(1-methylnaphtho[1,2-d]thiazol-2-ylidene)acetyl]coumarin, 3,3'-carbonylbis(6-methoxycoumarin), 3,3'-carbonylbis(7-acetoxycoumarin), 3,3'-carbonyl 3-(2-Benzothiazolyl)-7-(diethylamino)coumarin, 3-(2-Benzothiazolyl)-7-(dibutylamino)coumarin, 3-(2-Benzimidazolyl)-7-(diethylamino)coumarin, 3-(2-Benzothiazolyl)-7-(dioctylamino)coumarin, 3-acetyl-7-(dimethylamino)coumarin, 3,3'-carbonylbis(7-dibutylaminocoumarin), 3,3'-carbonyl-7-diethylaminocoumarin-7'-bis(butoxyethyl)aminocoumarin, 10-[3-[4-(dimethylamino)phenyl]-1-oxo-2-propenyl]-2,3,6,7-1,1,7,7-tetramethyl1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one, 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl 1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one and other compounds.

[0053] Among the coumarin compounds, 3,3'-carbonylbis(7-diethylaminocoumarin) and 3,3'-carbonylbis(7-dibutylaminocoumarin) are particularly suitable.

[0054] Specific examples of anthraquinones used as the photopolymerization initiator include anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1-bromoanthraquinone, 1,2-benzanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, and 1-hydroxyanthraquinone.

[0055] Specific examples of benzoin alkyl ethers used as the photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.

[0056] If the α-aminoketones used as the photopolymerization initiator are specifically exemplified, for example, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one etc. are mentioned.

[0057] Among the photopolymerization initiators, it is preferred to use at least one selected from the group consisting of (bis)acylphosphine oxides and their salts, α-diketones, and coumarin compounds. Thus, a composition showing sufficient photocurability can be obtained using any light source among halogen lamps, light emitting diodes (LEDs), and xenon lamps that have excellent photocurability in the visible and near-ultraviolet regions.

[0058] As the chemical polymerization initiator in the polymerization initiator contained in the medical dental curable composition of the present invention, an organic peroxide is preferably used. The organic peroxide used in the above-mentioned chemical polymerization initiator is not particularly limited, and known substances can be used. As representative organic peroxides, ketone peroxides, hydroperoxides, diacyl peroxides, dialkyl peroxides, peroxyketals, peroxyesters, peroxydicarbonates, etc. can be cited.

[0059] Specific examples of ketone peroxides used as chemical polymerization initiators include methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, methyl cyclohexanone peroxide, and cyclohexanone peroxide.

[0060] Specific examples of the hydroperoxide used as the chemical polymerization initiator include 2,5-dimethylhexane-2,5-dihydroperoxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.

[0061] Specific examples of the diacyl peroxide used as the chemical polymerization initiator include acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, decanoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 2,4-dichlorobenzoyl peroxide, and lauroyl peroxide.

[0062] Specific examples of dialkyl peroxides used as chemical polymerization initiators include di-tert-butyl peroxide, dicumyl peroxide, tert-butylcumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, 1,3-bis(tert-butylperoxide isopropyl)benzene, and 2,5-dimethyl-2,5-di(tert-butylperoxide)-3-hexyne.

[0063] Specific examples of peroxyketals used as chemical polymerization initiators include 1,1-bis(tert-butylperoxide)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxide)cyclohexane, 2,2-bis(tert-butylperoxide)butane, 2,2-bis(tert-butylperoxide)octane, and 4,4-bis(tert-butylperoxide)valeric acid-n-butyl ester.

[0064] Specific examples of peroxyesters used as chemical polymerization initiators include α-cumyl peroxyneodecanoate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, 2,2,4-trimethylamyl peroxy-2-ethylhexanoate, t-amyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, di-t-butyl peroxyisophthalate, di-t-butyl peroxyhexahydroterephthalate, t-butyl peroxy-3,3,5-trimethylhexanoate, t-butyl peroxyacetate, t-butyl peroxybenzoate, and t-butyl peroxymaleic acid.

[0065] If specific examples of peroxydicarbonates used as chemical polymerization initiators are given, for example, (di-3-methoxy) peroxydicarbonate, (di-2-ethylhexyl) peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, (di-2-ethoxyethyl) peroxydicarbonate and diallyl peroxydicarbonate can be mentioned.

[0066] Among organic peroxides, diacyl peroxides are preferably used in view of the overall balance among safety, storage stability and radical generating ability, and benzoyl peroxide is particularly preferably used.

[0067] Specific examples of the polymerization accelerator include amines, sulfinic acid and salts thereof, borate compounds, barbituric acid derivatives, triazine compounds, copper compounds, tin compounds, vanadium compounds, halogen compounds, aldehydes, and thiol compounds.

[0068] Amines used as polymerization accelerators are divided into aliphatic amines and aromatic amines. Specific examples of aliphatic amines include aliphatic primary amines such as n-butylamine, n-hexylamine, and n-octylamine; aliphatic secondary amines such as diisopropylamine, dibutylamine, and N-methyldiethanolamine; aliphatic tertiary amines such as N-methylethanolamine, N-ethyldiethanolamine, N-n-butyldiethanolamine, N-lauryldiethanolamine, 2-(dimethylamino)ethyl methacrylate, N-methyldiethanolamine dimethacrylate, N-ethyldiethanolamine dimethacrylate, triethanolamine monomethacrylate, triethanolamine dimethacrylate, triethanolamine trimethacrylate, triethanolamine, trimethylamine, triethylamine, and tributylamine. Among them, aliphatic tertiary amines are preferred from the viewpoint of curability and storage stability of the composition, and N-methyldiethanolamine and triethanolamine are more preferably used.

[0069] Specific examples of aromatic amines include N,N-bis(2-hydroxyethyl)-3,5-dimethylaniline, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N-bis(2-hydroxyethyl)-3,4-dimethylaniline, N,N-bis(2-hydroxyethyl)-4-ethylaniline, N,N-bis(2-hydroxyethyl)-4-isopropylaniline, N,N-bis(2-hydroxyethyl)-4-tert-butylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-isopropylaniline, N,N-bis(2-hydroxyethyl)-3,5-di-tert-butylaniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl- m-Toluidine, N,N-diethyl-p-toluidine, N,N-dimethyl-3,5-dimethylaniline, N,N-dimethyl-3,4-dimethylaniline, N,N-dimethyl-4-ethylaniline, N,N-dimethyl-4-isopropylaniline, N,N-dimethyl-4-tert-butylaniline, N,N-dimethyl-3,5-di-tert-butylaniline, 4-N,N-dimethylaminobenzoic acid ethyl ester, 4-N,N-dimethylaminobenzoic acid methyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, 4-N,N-dimethylaminobenzoic acid-2-(methacryloyloxy)ethyl ester, 4-N,N-dimethylaminobenzophenone, 4-dimethylaminobenzoic acid butyl ester, etc. Among them, from the viewpoint of imparting excellent curability to the composition, N,N-bis(2-hydroxyethyl)-p-toluidine, 4-N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid-n-butoxyethyl ester, and 4-N,N-dimethylaminobenzophenone can be cited.

[0070] Specific examples of sulfinic acid and salts thereof used as polymerization accelerators include p-toluenesulfinic acid, sodium p-toluenesulfinic acid, potassium p-toluenesulfinic acid, lithium p-toluenesulfinic acid, calcium p-toluenesulfinic acid, benzenesulfinic acid, sodium benzenesulfinic acid, potassium benzenesulfinic acid, lithium benzenesulfinic acid, calcium benzenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, sodium 2,4,6-trimethylbenzenesulfinic acid, potassium 2,4,6-trimethylbenzenesulfinic acid, lithium 2,4,6-trimethylbenzenesulfinic acid, calcium 2,4,6-trimethylbenzenesulfinic acid, ... Preferred are 2,4,6-triethylbenzenesulfinic acid, sodium 2,4,6-triethylbenzenesulfinic acid, potassium 2,4,6-triethylbenzenesulfinic acid, lithium 2,4,6-triethylbenzenesulfinic acid, calcium 2,4,6-triethylbenzenesulfinic acid, sodium 2,4,6-triisopropylbenzenesulfinic acid, potassium 2,4,6-triisopropylbenzenesulfinic acid, lithium 2,4,6-triisopropylbenzenesulfinic acid, calcium 2,4,6-triisopropylbenzenesulfinic acid, and particularly preferred are sodium benzenesulfinic acid, sodium p-toluenesulfinic acid, and sodium 2,4,6-triisopropylbenzenesulfinic acid.

[0071] As borate compounds used as polymerization accelerators, specific examples of borate compounds having one aromatic group in one molecule include trialkylphenylborane, trialkyl(p-chlorophenyl)borane, trialkyl(p-fluorophenyl)borane, trialkyl(3,5-bistrifluoromethyl)phenylborane, trialkyl[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]borane, trialkyl(p-nitrophenyl)borane, trialkyl(m-nitrophenyl)borane, trialkyl(p-butylphenyl)borane, trialkyl(p-butylphenyl)borane, trialkyl(p-chlorophenyl)borane, trialkyl(p-fluoro ... ) boron, trialkyl(m-butylphenyl)boron, trialkyl(p-butyloxyphenyl)boron, trialkyl(m-butyloxyphenyl)boron, trialkyl(p-octyloxyphenyl)boron and trialkyl(m-octyloxyphenyl)boron (the alkyl group is at least one selected from the group consisting of n-butyl, n-octyl and n-dodecyl, etc.), sodium salt, lithium salt, potassium salt, magnesium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt and butylquinolinium salt, etc.

[0072] In addition, if a borate compound having two aromatic groups in one molecule is specifically exemplified, for example, dialkyldiphenylborane, dialkyldi(p-chlorophenyl)borane, dialkyldi(p-fluorophenyl)borane, dialkyldi(3,5-bistrifluoromethyl)phenylborane, dialkyldi[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]borane, dialkyldi(p-nitrophenyl)borane, dialkyldi(m-nitrophenyl)borane, dialkyldi(p-butyl ...[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]borane, dialkyldi(p-butylphenyl)borane, dialkyldi Sodium salt, lithium salt, potassium salt, magnesium salt, tetrabutylammonium salt, tetramethylammonium salt, tetraethylammonium salt, methylpyridinium salt, ethylpyridinium salt, butylpyridinium salt, methylquinolinium salt, ethylquinolinium salt and butylquinolinium salt of (m-butylphenyl)boron, dialkyldi(p-butyloxyphenyl)boron, dialkyldi(m-butyloxyphenyl)boron, dialkyldi(p-octyloxyphenyl)boron and dialkyldi(m-octyloxyphenyl)boron (the alkyl group is at least one selected from the group consisting of n-butyl, n-octyl and n-dodecyl, etc.).

[0073] Furthermore, if a borate compound having three aromatic groups in a molecule is specifically exemplified, for example, monoalkyltriphenylborane, monoalkyltri(p-chlorophenyl)borane, monoalkyltri(p-fluorophenyl)borane, monoalkyltri(3,5-bistrifluoromethyl)phenylborane, monoalkyltri[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]borane, monoalkyltri(p-nitrophenyl)borane, monoalkyltri(m-nitrophenyl)borane, monoalkyltri(p-butylphenyl)borane, Sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, butylquinolinium salts, and the like of monoalkyltri(m-butylphenyl)borane, monoalkyltri(p-butyloxyphenyl)borane, monoalkyltri(p-octyloxyphenyl)borane, and monoalkyltri(m-octyloxyphenyl)borane (the alkyl group is one selected from n-butyl, n-octyl, or n-dodecyl, etc.).

[0074] Further, if the borate compound having four aromatic groups in the molecule is specifically exemplified, for example, tetraphenylboron, tetra(p-chlorophenyl)boron, tetra(p-fluorophenyl)boron, tetra(3,5-bistrifluoromethyl)phenylboron, tetra(3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl)boron, tetra(p-nitrophenyl)boron, tetra(m-nitrophenyl)boron, tetra(p-butylphenyl)boron, tetra(m-butylphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(m-butyloxyphenyl)boron, tetra(p-octyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(m-butyloxyphenyl)boron, tetra(p-octyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-octyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-butyloxyphenyl)boron, tetra(p-octyloxyphenyl)boron, tetra(p-nitrophenyl)boron, tetra(m-nitro ... The invention also includes sodium salts, lithium salts, potassium salts, magnesium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts and butylquinolinium salts of (m-butyloxyphenyl)triphenylboron, (m-butyloxyphenyl)triphenylboron, (p-butyloxyphenyl)triphenylboron, (m-octyloxyphenyl)triphenylboron and (p-octyloxyphenyl)triphenylboron, and the like.

[0075] Among these aryl borate compounds, from the viewpoint of storage stability, it is more preferable to use a borate compound having three or four aryl groups in one molecule. In addition, these aryl borate compounds may be used alone or in combination of two or more.

[0076] Specific examples of the barbituric acid derivatives used as the polymerization accelerator include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethylbarbituric acid, 1,3-dimethyl-5-cyclopentylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-1-ethylbarbituric acid, 1-benzyl-5- Phenylbarbituric acid, 5-methylbarbituric acid, 5-propylbarbituric acid, 1,5-diethylbarbituric acid, 1-ethyl-5-methylbarbituric acid, 1-ethyl-5-isobutylbarbituric acid, 1,3-diethyl-5-butylbarbituric acid, 1-cyclohexyl-5-methylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-cyclohexyl-5-octylbarbituric acid, 1-cyclohexyl-5-hexylbarbituric acid, 5-butyl-1-cyclohexylbarbituric acid, 1-benzyl-5-phenylbarbituric acid and thiobarbituric acids, and salts thereof (particularly preferably alkali metals or alkaline earth metals). Examples of the salts of these barbituric acids include sodium 5-butylbarbiturate, sodium 1,3,5-trimethylbarbiturate and sodium 1-cyclohexyl-5-ethylbarbiturate.

[0077] Specific examples of particularly suitable barbituric acid derivatives include 5-butylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, and sodium salts of these barbituric acids.

[0078] Specific examples of triazine compounds used as polymerization accelerators include 2,4,6-tris(trichloromethyl)-s-triazine, 2,4,6-tris(tribromomethyl)-s-triazine, 2-methyl-4,6-bis(trichloromethyl)-s-triazine, 2-methyl-4,6-bis(tribromomethyl)-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methylthiophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(p-methylthiophenyl)-4,6-bis(trichloromethyl)-s-triazine. s-triazine, 2-(2,4-dichlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-bromophenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-n-propyl-4,6-bis(trichloromethyl)-s-triazine, 2-(α,α,β-trichloroethyl)-4,6-bis(trichloromethyl)-s-triazine, 2-phenylvinyl-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-methoxyphenyl)vinyl] ]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(o-methoxyphenyl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(p-butoxyphenyl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4-dimethoxyphenyl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-(3,4,5-trimethoxyphenyl)vinyl]-4,6-bis(trichloromethyl)-s-triazine, 2-(1-naphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-biphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-bis(2-hydroxyethyl)amino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-ethylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N-hydroxyethyl-N-methylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, 2-[2-{N,N-diallylamino}ethoxy]-4,6-bis(trichloromethyl)-s-triazine, and the like.

[0079] From the perspective of polymerization activity, 2,4,6-tris(trichloromethyl)-s-triazine is particularly preferred among the triazine compounds exemplified above, and from the perspective of storage stability, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenyl)-4,6-bis(trichloromethyl)-s-triazine are particularly preferred. The above triazine compounds may be used alone or in combination of two or more.

[0080] Specific examples of the copper compound used as the polymerization accelerator include copper acetylacetonate, copper acetate, copper oleate, copper chloride, copper bromide, and the like.

[0081] Specific examples of tin compounds used as polymerization accelerators include di-n-butyltin dimaleate, di-n-octyltin dimaleate, di-n-octyltin dilaurate, di-n-butyltin dilaurate, etc. Particularly suitable tin compounds are di-n-octyltin dilaurate and di-n-butyltin dilaurate.

[0082] The vanadium compound used as the polymerization accelerator is preferably a vanadium compound with a valence of IV and / or V. Specific examples of vanadium compounds with a valence of IV and / or V include vanadium (IV) tetroxide, vanadium oxide acetylacetonate (IV), vanadyl oxalate (IV), vanadyl sulfate (IV), oxybis(1-phenyl-1,3-butanedione)vanadium (IV), bis(maltol)oxyvanadium (IV), vanadium pentoxide (V), sodium metavanadate (V), ammonium metavanadate (V), and the like.

[0083] Specific examples of the halogen compound used as the polymerization accelerator include dilauryldimethylammonium chloride, lauryldimethylbenzylammonium chloride, benzyltrimethylammonium chloride, tetramethylammonium chloride, benzyldimethylhexadecylammonium chloride, and dilauryldimethylammonium bromide.

[0084] If the aldehydes used as the polymerization accelerator are specifically exemplified, for example, terephthalaldehyde, benzaldehyde derivatives, etc. Examples of benzaldehyde derivatives include dimethylaminobenzaldehyde, p-methyloxybenzaldehyde, p-ethyloxybenzaldehyde, p-n-octyloxybenzaldehyde, etc. Among them, p-n-octyloxybenzaldehyde is preferably used from the viewpoint of curability.

[0085] Specific examples of the thiol compound used as the polymerization accelerator include 3-mercaptopropyltrimethoxysilane, 2-mercaptobenzoxazole, decanethiol, and thiobenzoic acid.

[0086] The components that can be contained in the medical and dental curable composition of the present invention are arbitrary, and specific examples thereof include colorants such as dyes and pigments, thickeners, and aromatics.

[0087] Example

[0088] The method for producing the silane coupling agent of the present invention and the method for preparing and the physical properties of the medical and dental curable composition containing the same are described in detail, but the present invention is not limited to these descriptions at all.

[0089] (Synthesis Example 11) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0090] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 300mL of toluene, 16.8g (0.10mol) of 1,6-diisocyanate hexane, and 47.9mg of p-methoxyphenol were added to dissolve them. Next, 13.0g (0.1mol) of 2-hydroxyethyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-hydroxyethyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained unchanged and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactant was returned to room temperature, and HPLC and FT-IR measurements were performed. It should be noted that the sample at this time was a very small amount of a pipette and the solvent was removed by an evaporator. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,6-diisocyanate hexane and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((6-isocyanate hexyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 298.34). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1 The absorption derived from the carbamate group was newly confirmed. Next, 18.0 g (0.10 mol) of 3-(trimethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 29.8 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((6-isocyanate hexyl)carbamoyl)oxy)ethyl methacrylate and 3-(trimethoxysilyl)propane-1-ol, which are raw materials, disappeared, and a new peak was confirmed: 3,3-dimethoxy-8,17-dioxo-2,7,18-trioxa-9,16-diaza-3-silaicosane-20-yl methacrylate (molecular weight 478.61). In addition, the results of FT-IR measurement are as follows: 2280-2250cm -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0091] [Chemical formula 8]

[0092]

[0093] (Synthesis Example 12) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0094] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 300mL of toluene, 16.8g (0.10mol) of 1,6-diisocyanate hexane, and 52.3mg of p-methoxyphenol were added to dissolve them. Then, 17.4g (0.1mol) of 2-(2-hydroxyethoxy)ethyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-(2-hydroxyethoxy)ethyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained unchanged and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactant was returned to room temperature, and HPLC and FT-IR measurements were performed. It should be noted that the sample at this time was a very small amount of a pipette and the solvent was removed by an evaporator. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,6-diisocyanate hexane and 2-(2-hydroxyethoxy)ethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(2-(((6-isocyanate hexyl)carbamoyl)oxy)ethoxy)ethyl methacrylate (molecular weight 342.39). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1The absorption derived from the carbamate group was newly confirmed. Next, 18.0 g (0.10 mol) of 3-(trimethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 34.2 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(2-(((6-isocyanate hexyl)carbamoyl)oxy)ethoxy)ethyl methacrylate and 3-(trimethoxysilyl)propane-1-ol, which are raw materials, disappeared, and a new peak was confirmed: 3,3-dimethoxy-8,17-dioxo-2,7,18,21-tetraoxa-9,16-diaza-3-silatricosan-23-yl methacrylate (molecular weight 522.67). In addition, the results of FT-IR measurement are as follows: 2280-2250cm -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0095] [Chemical formula 9]

[0096]

[0097] (Synthesis Example 13) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0098] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 300mL of toluene, 16.8g (0.10mol) of 1,6-diisocyanate hexane, and 52.1mg of p-methoxyphenol were added to dissolve them. Next, 17.2g (0.1mol) of 5-hydroxypentyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 5-hydroxypentyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained unchanged and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactant was returned to room temperature, and HPLC and FT-IR measurements were performed. It should be noted that the sample at this time was a very small amount of a pipette and the solvent was removed by an evaporator. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,6-diisocyanate hexane and 5-hydroxypentyl methacrylate as raw materials disappeared, and a new peak was confirmed: 5-(((6-isocyanate hexyl)carbamoyl)oxy)pentyl methacrylate (molecular weight 340.42). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1 The absorption derived from the carbamate group was newly confirmed. Next, 18.0 g (0.10 mol) of 3-(trimethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 34.0 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 5-(((6-isocyanate hexyl)carbamoyl)oxy)pentyl methacrylate and 3-(trimethoxysilyl)propane-1-ol, which are raw materials, disappeared, and a new peak was confirmed: 3,3-dimethoxy-8,17-dioxo-2,7,18-trioxa-9,16-diaza-3-silatricosan-23-yl methacrylate (molecular weight 520.70). In addition, the results of FT-IR measurement are as follows: 2280-2250cm -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0099] [Chemical formula 10]

[0100]

[0101] (Synthesis Example 14) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0102] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 300mL of toluene, 15.4g (0.10mol) of 1,5-diisocyanate pentane, and 46.5mg of p-methoxyphenol were added to dissolve them. Next, 13.0g (0.1mol) of 2-hydroxyethyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-hydroxyethyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained unchanged and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactant was returned to room temperature, and HPLC and FT-IR measurements were performed. It should be noted that the sample at this time was a very small amount of a pipette and the solvent was removed by an evaporator. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,5-diisocyanate pentane and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((5-isocyanate pentyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 284.31). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1The absorption derived from the carbamate group was newly confirmed. Next, 18.0 g (0.10 mol) of 3-(trimethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 28.4 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((5-isocyanate pentyl)carbamoyl)oxy)ethyl methacrylate and 3-(trimethoxysilyl)propane-1-ol, which are raw materials, disappeared, and a new peak was confirmed: 3,3-dimethoxy-8,16-dioxo-2,7,17-trioxa-9,15-diaza-3-silanonadecan-19-yl methacrylate (molecular weight 464.59). In addition, the results of FT-IR measurement are as follows: 2280-2250cm -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0103] [Chemical formula 11]

[0104]

[0105] (Synthesis Example 15) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0106] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 300mL of toluene, 12.6g (0.10mol) of 1,2-diisocyanate propane, and 43.7mg of p-methoxyphenol were added to dissolve them. Next, 13.0g (0.1mol) of 2-hydroxyethyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-hydroxyethyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained unchanged and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactant was returned to room temperature, and HPLC and FT-IR measurements were performed. It should be noted that the sample at this time was a very small amount of a pipette and the solvent was removed by an evaporator. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,2-diisocyanate propane and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((1-isocyanate propane-2-yl)carbamoyl)oxy)ethyl methacrylate (molecular weight 256.26). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1 The absorption derived from the carbamate group was newly confirmed. Next, 18.0 g (0.10 mol) of 3-(trimethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 25.6 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((1-isocyanatepropane-2-yl)carbamoyl)oxy)ethyl methacrylate and 3-(trimethoxysilyl)propane-1-ol, which are raw materials, disappeared, and a new peak was confirmed: 3,3-dimethoxy-11-methyl-8,13-dioxo-2,7,14-trioxa-9,12-diaza-3-silahexadecane-16-yl methacrylate (molecular weight 436.53). In addition, the results of FT-IR measurement are as follows: 2280-2250cm -1 Isocyanate absorption, 3300cm -1The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0107] [Chemical formula 12]

[0108]

[0109] (Comparative Synthesis Example 11) Comparative Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group 11

[0110] In a four-necked flask (100 mL volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 10-undecene-1-ol: 17.0 g (0.10 mol) and p-methoxyphenol: 16.3 mg (equivalent to 500 ppm) were added and dissolved. Next, 2-isocyanate ethyl methacrylate: 15.5 g (0.10 mol) was weighed in the dropping funnel. The four-necked flask was immersed in an oil bath heated to 75°C, and 2-isocyanate ethyl methacrylate was added dropwise while stirring at an internal temperature not exceeding 80°C. After the addition was completed, the temperature of the oil bath was maintained constant and the reaction was continued for 12 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactants were returned to room temperature, and HPLC and FT-IR measurements were performed. The analysis conditions of HPLC determination are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR determination was performed using the ATR method. The results of HPLC determination are as follows: the peaks of 10-undecene-1-ol and 2-isocyanatoethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-((10-undecenyloxy)carbonylamino)ethyl methacrylate (molecular weight 325.4). In addition, the results of FT-IR determination are as follows: 2280~2250cm -1 Isocyanate absorption and 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1The absorption derived from the carbamate group was newly confirmed. Next, 4.9 mg (equivalent to 100 ppm) of platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane was added to a four-necked flask containing 32.5 g (0.10 mol) of the compound synthesized by the above operation, and stirred thoroughly to make it uniform. Separately, 16.4 g (0.10 mol) of triethoxysilane was weighed in a dropping funnel. In a four-necked flask, triethoxysilane was added dropwise at room temperature while stirring at an internal temperature not exceeding 35°C. After the addition was completed, the reaction was continued at room temperature for 12 hours and ripened. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-((10-undecenyloxy)carbonylamino)ethyl methacrylate and triethoxysilane as raw materials disappeared, and a new peak was confirmed: 4,4-diethoxy-17-oxo-3,16-dioxa-18-aza-4-silaicosane-20-yl methacrylate (molecular weight 489.7). In addition, the results of FT-IR measurement are as follows: a peak at 2190 cm -1 The chemical structural formula of the compound synthesized in this example is recorded below.

[0111] [Chemical formula 13]

[0112]

[0113] Examples 11-1 to 11-5 (Preparation of composite resin for medical and dental use - Inorganic filling rate 70 wt%)

[0114] Using the polymerizable silane coupling agent synthesized in Synthesis Examples 11 to 15, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resin for medical and dental use are performed. The specific surface modification method is described below. The amount of synthesized silane coupling agent described in Table 11-1 is dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g are added. After that, an electromagnetic stirrer is placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion is completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution are added under stirring, and the flask is immersed in a boiling water bath for 5 hours and refluxed. After the reflux was completed, the internal temperature was returned to room temperature, and the binder solution (UDMA, 2G) and photopolymerization initiator listed in Table 11-1 were added under light-shielding conditions. After uniform stirring, the ethanol was distilled off using an evaporator. After that, the solvent was completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company at 1000rpm-5KPa-15min to obtain a medical and dental composite resin.

[0115] Examples 12-1 to 12-5, (Preparation of composite resin for medical and dental use - Inorganic filling rate 85 wt%)

[0116] Using the polymerizable silane coupling agent synthesized in Synthesis Examples 11 to 15, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resin for medical and dental use are performed. The specific surface modification method is described below. The amount of the synthesized silane coupling agent described in Table 11-2 is dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g are added. After that, an electromagnetic stirrer is placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion is completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution are added under stirring, and the flask is immersed in a boiling water bath for 5 hours and refluxed. After the reflux, the internal temperature was returned to room temperature, and the binder solution (UDMA, 2G) and photopolymerization initiator listed in Table 11-2 were added under light-shielding conditions. After uniform stirring, the ethanol was distilled off using an evaporator. After that, the solvent was completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company at 1000rpm-5KPa-15min to obtain a medical and dental composite resin.

[0117] Comparative Examples 11-1 to 11-3 (Preparation of composite resin for medical and dental use - Inorganic filling rate 70 wt%)

[0118] Using commercially available polymerizable silane coupling agents and the silane coupling agents synthesized in Comparative Synthesis Example 11, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resin for medical and dental use were performed. The specific surface modification method is described below. The amount of silane coupling agent described in Table 11-1 was dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g were added. After that, an electromagnetic stirrer was placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion was completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution were added under stirring, and the flask was immersed in a boiling water bath for 5 hours and refluxed. After the reflux was completed, the internal temperature was returned to room temperature, and the binder solution (UDMA, 2G) and photopolymerization initiator listed in Table 11-1 were added under light-shielding conditions. After uniform stirring, the ethanol was distilled off using an evaporator. After that, the solvent was completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company at 1000rpm-5KPa-15min to obtain a medical and dental composite resin.

[0119] Comparative Examples 12-1 to 12-3 (Preparation of composite resin for medical and dental use - Inorganic filling rate 85 wt%)

[0120] Using commercially available polymerizable silane coupling agents and the silane coupling agents synthesized in Comparative Synthesis Example 11, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resin for medical and dental use were performed. The specific surface modification method is described below. The commercially available silane coupling agent in the amount described in Table 11-2 was dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g were added. After that, an electromagnetic stirrer was placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion was completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution were added under stirring, and the flask was immersed in a boiling water bath for 5 hours and refluxed. After the reflux, the internal temperature was returned to room temperature, and the binder solution (UDMA, 2G) and photopolymerization initiator listed in Table 11-2 were added under light-shielding conditions. After uniform stirring, the ethanol was distilled off using an evaporator. After that, the solvent was completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company at 1000rpm-5KPa-15min to obtain a medical and dental composite resin.

[0121] (Synthesis Example 21) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0122] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, add 500mL of toluene, 27.5g (0.11mol) of bis(4-isocyanatephenyl)methane, and 60.3mg of p-methoxyphenol to dissolve them. Next, weigh 14.3g (0.11mol) of 2-hydroxyethyl methacrylate in a beaker, add 150mL of toluene, stir well, and transfer to the dropping funnel. Immerse the four-necked flask in an oil bath heated to 80°C, and add 2-hydroxyethyl methacrylate dropwise while stirring. After the addition is completed, the temperature of the oil bath is maintained constant and the reaction is continued for 24 hours for aging. After the aging is completed, the four-necked flask is removed from the oil bath, the reactants are returned to room temperature, and HPLC and FT-IR measurements are performed. The analysis conditions of HPLC determination are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR determination was performed using the ATR method. The results of HPLC determination are as follows: bis(4-isocyanatephenyl)methane and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((4-(4-isocyanatebenzyl)phenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 380.4). In addition, the results of FT-IR determination are as follows: 2280~2250cm-1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1 The absorption derived from the carbamate group was newly confirmed. Next, 22.2 g (0.10 mol) of 3-(triethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 38.0 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((4-(4-isocyanate benzyl)phenyl)carbamoyl)oxy)ethyl methacrylate and 3-(triethoxysilyl)propane-1-ol, which are raw materials, disappeared, and a new peak was confirmed: 2-(((4-(4-(((3-(triethoxysilyl)propoxy)carbonyl)amino)benzyl)phenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 602.76). In addition, the results of FT-IR measurement are as follows: 2280-2250cm -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0123] [Chemical formula 14]

[0124]

[0125] (Synthesis Example 22) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0126] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 500mL of toluene, 30.6g (0.11mol) of 4,4'-(propane-2,2-diyl)bis(isocyanate benzene), and 63.1mg of p-methoxyphenol were added to dissolve them. Next, 14.3g (0.11mol) of 2-hydroxyethyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-hydroxyethyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained constant and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactant was returned to room temperature, and HPLC and FT-IR measurements were performed. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 4,4'-(propane-2,2-diyl)bis(isocyanate benzene) and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((4-(2-(4-isocyanate phenyl)propane-2-yl)phenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 408.45). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1 The absorption derived from the carbamate group was newly confirmed. Next, 22.2 g (0.10 mol) of 3-(triethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 40.8 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((4-(2-(4-isocyanatephenyl)propane-2-yl)phenyl)carbamoyl)oxy)ethyl methacrylate and 3-(triethoxysilyl)propane-1-ol as raw materials disappeared, and a new peak was confirmed: 2-(((4-(2-(4-(((3-(triethoxysilyl)propoxy)carbonyl)amino)phenyl)propane-2-yl)phenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 630.81). In addition, the results of FT-IR measurement were confirmed as follows: 2280~2250cm -1 Isocyanate absorption, 3300cm -1The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0127] [Chemical formula 15]

[0128]

[0129] (Synthesis Example 23) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0130] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 500mL of toluene, 19.2g (0.11mol) of 1,3-diisocyanate-2-methylbenzene, and 52.7mg of p-methoxyphenol were added to dissolve them. Next, 14.3g (0.11mol) of 2-hydroxyethyl methacrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-hydroxyethyl methacrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained constant and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactants were returned to room temperature, and HPLC and FT-IR measurements were performed. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,3-diisocyanate-2-methylbenzene and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((3-isocyanate-2-methylphenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 304.3). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1The absorption derived from the carbamate group was newly confirmed. Next, 22.2 g (0.10 mol) of 3-(triethoxysilyl)propane-1-ol was added dropwise to a toluene solution containing 30.4 g (0.10 mol) of the precursor compound synthesized by the above operation while stirring. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80° C. in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and aging was performed. After the aging was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((3-isocyanate-2-methylphenyl)carbamoyl)oxy)ethyl methacrylate and 3-(triethoxysilyl)propane-1-ol as raw materials disappeared, and a new peak was confirmed: 2-(((2-methyl-3-(((3-(triethoxysilyl)propoxy)carbonyl)amino)phenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 526.66). The results of FT-IR measurement are as follows: -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0131] [Chemical formula 16]

[0132]

[0133] (Synthesis Example 24) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0134] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, 500mL of toluene, 21.4g (0.11mol) of 1,3-bis(isocyanatemethyl)cyclohexane, and 49.1mg of p-methoxyphenol were added to dissolve them. Next, 12.8g (0.11mol) of 2-hydroxyethyl acrylate was weighed in a beaker, and 150mL of toluene was added, stirred thoroughly, and transferred to the dropping funnel. The four-necked flask was immersed in an oil bath heated to 80°C, and 2-hydroxyethyl acrylate was added dropwise while stirring. After the addition was completed, the temperature of the oil bath was maintained constant and the reaction was continued for 24 hours for aging. After the aging was completed, the four-necked flask was removed from the oil bath, the reactants were returned to room temperature, and HPLC and FT-IR measurements were performed. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 1,3-bis(isocyanatemethyl)cyclohexane and 2-hydroxyethyl acrylate as raw materials disappeared, and a new peak was confirmed: 2-((((3-(isocyanatemethyl)cyclohexyl)methyl)carbamoyl)oxy)ethyl acrylate (molecular weight 310.35). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1 The absorption derived from the carbamate group was newly confirmed. Next, 22.2 g (0.10 mol) of 3-(triethoxysilyl)propane-1-ol was added dropwise while stirring to a toluene solution containing 31.0 g (0.10 mol) of the precursor compound synthesized by the above operation. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80°C in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and ripening was performed. After the ripening was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-((((3-(isocyanatemethyl)cyclohexyl)methyl)carbamoyl)oxy)ethyl acrylate and 3-(triethoxysilyl)propane-1-ol as raw materials disappeared, and a new peak was confirmed: 2-((((3-(3,3-dimethoxy-8-oxo-2,7-dioxa-9-aza-3-siladecan-10-yl)cyclohexyl)methyl)carbamoyl)oxy)ethyl acrylate (molecular weight 490.63). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0135] [Chemical formula 17]

[0136]

[0137] (Synthesis Example 25) Synthesis of Silane Coupling Agent Having a Radical Polymerizable Group

[0138] In a four-necked flask (1L volume) equipped with a stirring blade, a thermometer, a dropping funnel, and a condenser, add 500mL of toluene, 19.2g (0.11mol) of 2,4-diisocyanate-1-methylbenzene, and 52.7mg of p-methoxyphenol to dissolve them. Next, weigh 14.3g (0.11mol) of 2-hydroxyethyl methacrylate in a beaker, add 150mL of toluene, stir well, and transfer to the dropping funnel. Immerse the four-necked flask in an oil bath heated to 80°C, and add 2-hydroxyethyl methacrylate dropwise while stirring. After the addition is completed, the temperature of the oil bath is maintained unchanged and the reaction is continued for 24 hours for aging. After the aging is completed, the four-necked flask is removed from the oil bath, the reactant is returned to room temperature, and HPLC and FT-IR measurements are performed. The analysis conditions of HPLC measurement are as follows: column ZORBAX-ODS, acetonitrile / distilled water = 7 / 3, flow rate 0.5 mL / min, multi-scan UV detector, RI detector, MS detector. FT-IR measurement was performed using the ATR method. The results of HPLC measurement are as follows: 2,4-diisocyanate-1-methylbenzene and 2-hydroxyethyl methacrylate as raw materials disappeared, and a new peak was confirmed: 2-(((5-isocyanate-2-methylphenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 304.30). In addition, the results of FT-IR measurement are as follows: 2280~2250cm -1 The isocyanate absorption intensity decreases and the 3300 cm -1 The disappearance of the hydroxyl absorption near 1250cm -1The absorption derived from the carbamate group was newly confirmed. Next, 22.2 g (0.10 mol) of 3-(triethoxysilyl)propane-1-ol was added dropwise to a toluene solution containing 30.4 g (0.10 mol) of the precursor compound synthesized by the above operation while stirring. It should be noted that the reaction was carried out by immersing in an oil bath heated to 80° C. in the same manner as in the first stage. After the addition was completed, the reaction was continued for 24 hours and aging was performed. After the aging was completed, HPLC and FT-IR measurements were performed. The results of HPLC measurement are as follows: the peaks of 2-(((5-isocyanate-2-methylphenyl)carbamoyl)oxy)ethyl methacrylate and 3-(triethoxysilyl)propane-1-ol as raw materials disappeared, and a new peak was confirmed: 2-(((2-methyl-5-(((3-(triethoxysilyl)propoxy)carbonyl)amino)phenyl)carbamoyl)oxy)ethyl methacrylate (molecular weight 526.66). The results of FT-IR measurement are as follows: -1 Isocyanate absorption, 3300cm -1 The chemical structural formula of the compound synthesized in this synthesis example is described below.

[0139] [Chemical formula 18]

[0140]

[0141] Examples 21-1 to 21-7 (Preparation of composite resin for medical and dental use)

[0142] Using the polymerizable silane coupling agents synthesized in Synthesis Examples 21 to 25 and 11 to 12, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resins for medical dentistry are performed. The specific surface modification method is described below. The amount of synthesized silane coupling agent described in Table 21-1 is dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g are added. After that, an electromagnetic stirrer is placed and stirred for 10 minutes, and further dispersed in a 28KHz-150W ultrasonic disperser for 5 minutes. After the dispersion is completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution are added under stirring, and the flask is immersed in a boiling water bath for 5 hours and refluxed. After the reflux is completed, the internal temperature is restored to room temperature, and the binder solution (Monomer-A, -C) and the photopolymerization initiator recorded in Table 21-1 are added under light protection, and after uniform stirring, the ethanol is distilled off using an evaporator. Then, the solvent is completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company under the conditions of 1000rpm-5KPa-15min to obtain a medical and dental composite resin. It should be noted that the chemical structure of Monomer-A, -C is recorded in [Chemical Formula 19].

[0143] Examples 22-1 to 22-7 (Preparation of composite resin for medical and dental use)

[0144] Using the polymerizable silane coupling agents synthesized in Synthesis Examples 21 to 25 and 11 to 12, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ryomori Co., Ltd.) and preparation of composite resins for medical dentistry are performed. The specific surface modification method is described below. The amount of the synthesized silane coupling agent described in Table 21-2 is dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g are added. After that, an electromagnetic stirrer is placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion is completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution are added under stirring, and the flask is immersed in a boiling water bath for 5 hours and refluxed. After the reflux is completed, the internal temperature is restored to room temperature, and the binder liquid (Monomer-B, -C) and the photopolymerization initiator recorded in Table 21-2 are added under light protection, and after uniform stirring, the ethanol is distilled off using an evaporator. After that, the solvent is completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company under the conditions of 1000rpm-5KPa-15min to obtain a medical and dental composite resin. It should be noted that the chemical structure of Monomer-B, -C is recorded in [Chemical Formula 19].

[0145] [Chemical formula 19]

[0146]

[0147] Comparative Example 21-1, (Preparation of Composite Resin for Medical and Dental Use)

[0148] Using the silane coupling agent synthesized in Comparative Synthesis Example 11, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resin for medical and dental use were performed. The specific surface modification method is described below. The amount of silane coupling agent described in Table 21-1 was dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g were added. After that, an electromagnetic stirrer was placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion was completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution were added under stirring, and the flask was immersed in a boiling water bath for 5 hours and refluxed. After the reflux was completed, the internal temperature was returned to room temperature, and the binder solution (Monomer-A, -C) and photopolymerization initiator described in Table 21-1 were added under light protection, and after uniform stirring, the ethanol was distilled off using an evaporator. After that, the solvent was completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company under the conditions of 1000rpm-5KPa-15min to obtain a medical and dental composite resin.

[0149] Comparative Example 22-1, (Preparation of Composite Resin for Medical and Dental Use)

[0150] Using the silane coupling agent synthesized in Comparative Synthesis Example 11, surface modification of OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Ronson Co., Ltd.) and preparation of composite resin for medical dentistry were performed. The specific surface modification method is described below. The amount of silane coupling agent described in Table 21-2 was dissolved in 300 mL of ethanol and placed in a 500 mL eggplant-shaped bottle to which OX-50: 15.0 g and Fuselex: 45.0 g were added. After that, an electromagnetic stirrer was placed and stirred for 10 minutes, and further dispersed in an ultrasonic disperser at 28KHz-150W for 5 minutes. After the dispersion was completed, 2.4 g of distilled water and 1.2 g of a 1wt% phosphoric acid aqueous solution were added under stirring, and the flask was immersed in a boiling water bath for 5 hours and refluxed. After the reflux was completed, the internal temperature was returned to room temperature, and the binder solution (Monomer-B, -C) and photopolymerization initiator described in Table 1-2 were added under light protection, and after uniform stirring, the ethanol was distilled off using an evaporator. After that, the solvent was completely removed using Planetary Vacuum mixer ARV-310 manufactured by Thinky Company under the conditions of 1000rpm-5KPa-15min to obtain a medical and dental composite resin.

[0151] Bending strength test

[0152] For the medical and dental composite resins prepared in Examples 11-1 to 11-5, 12-1 to 12-5, 21-1 to 21-7, 22-1 to 22-7, Comparative Examples 11-1 to 11-3, 12-1 to 12-3, 21-1, and 22-1, cured products were prepared in accordance with ISO 4049, and the bending strength was determined using an Instron universal testing machine (Instron 5567, manufactured by Instron Corporation). The photopolymerization was performed by irradiating light for 30 seconds using Griplight II manufactured by Shofu Co., Ltd.

[0153] Color stability test of silane coupling agent

[0154] 9.0 mL of the silane coupling agents synthesized in Synthesis Examples 11 to 15 and 21 to 25, Comparative Synthesis Example 11, and two types of polymerizable silane coupling agents commercially available from Shin-Etsu Chemical Co., Ltd. [KBM-503: 3-(trimethoxysilyl)propyl methacrylate (also referred to as "C-SC11"), KBE-503: 3-(triethoxysilyl)propyl methacrylate (also referred to as "C-SC12")] were transferred to a 10 mL colorless transparent glass vial, and the Hazen color number was measured. In addition, the Hazen color number was measured after the same sample was stored in a thermostat at 50° C. in the dark for 1 month.

[0155] Color stability test of prepared medical and dental composite resin cured body

[0156] The prepared medical and dental composite resin was cured (circular disk with a diameter of 15 mmφ and a thickness of 1.0 mm) according to ISO4049, and the color stability of the cured product was determined using a light resistance tester (Atlas SUNTEST CPS+, manufactured by Toyo Seiki Seisaku-sho Co., Ltd.). It should be noted that the photopolymerization was performed by irradiating light for 30 seconds using Griplight II manufactured by Matsukaze Co., Ltd.

[0157] Evaluation results

[0158] Evaluation Results Table 12-1 shows the results of the bending strength test of the medical dental composite resins prepared based on Examples 11-1 to 11-5 and 12-1 to 12-5. These results show that the medical dental composite resins containing microparticles prepared using the silane coupling agent synthesized according to the present invention (Synthesis Examples 11 to 15) have significantly higher bending strength characteristics than the medical dental composite resins using the silane coupling agents used in the past (Comparative Examples 11-1 to 11-3 and 12-1 to 12-3). It can be seen that the fracture energy characteristics are particularly significantly improved. That is, by surface-treating the inorganic filler with the silane coupling agent of the present invention, the medical dental composite resin cured body exhibits toughness, and as a result, the medical dental composite resin is given high mechanical strength. It is speculated that this is the result of the addition of long-chain alkylene groups and multiple carbamate groups. The above evaluation results (bending strength test results) show that the silane coupling agent having a long-chain alkylene group and a plurality of carbamate groups of the present invention can be applied to and provided in general industries such as medical and dental curable compositions having high mechanical strength that cannot be achieved with the prior art, bonding to electronic component material substrates including smartphones, bonding to automotive raw materials, etc.

[0159] Next, the measurement results of the Hazen color number obtained in the color tone stability test are shown in Table 12-2. These measurement results show that the Hazen color number of the polymerizable silane coupling agent (SC11 to SC15) containing no platinum complex synthesized in Synthesis Examples 11 to 15 and two types of polymerizable silane coupling agents commercially available from Shin-Etsu Chemical Co., Ltd. [3-(trimethoxysilyl)propyl methacrylate (C-SC11), 3-(triethoxysilyl)propyl methacrylate (C-SC12)] did not show significant differences just after synthesis and just after purchase, and after being stored in the dark at 50°C for 1 month. In contrast, the Hazen color number of the polymerizable silane coupling agent (C-SC13) containing a platinum complex synthesized in Comparative Synthesis Example 11 showed significant differences just after synthesis and after being stored in the dark at 50°C for 1 month. It is believed that this significant color tone change originates from the residual platinum complex.

[0160] Next, the measurement results of the color tone stability of the cured product are shown in Table 12-3. These measurement results show that the cured medical and dental composite resin containing inorganic filler material surface-modified using the polymerizable silane coupling agent containing no platinum complex synthesized in Synthesis Examples 11 to 15 and two polymerizable silane coupling agents commercially available from Shin-Etsu Chemical Co., Ltd. [3-(trimethoxysilyl)propyl methacrylate, 3-(triethoxysilyl)propyl methacrylate] has no significant difference in color tone change. In contrast, the cured medical and dental composite resin containing inorganic filler material surface-modified using the polymerizable silane coupling agent containing a platinum complex synthesized in Comparative Synthesis Example 1 has a significant difference in color tone change, and yellowing is significant.

[0161] These test results show that the discoloration caused by the important precious metals that cannot be confirmed aesthetically in the medical dental curable composition is epoch-making. In addition, the precious metals as hydrosilylation catalysts are not used at all during synthesis, so that the reduction of manufacturing costs becomes possible. And then, by using a compound with isocyanate groups at both ends as a reaction matrix, the reagent solubility of organic solvents is significantly improved during synthesis, so that, compared with 1-10-decanediol, carbamate reaction can be carried out at a high temperature. This is also related to the shortening of the reaction time, which becomes the result related to the reduction of manufacturing costs.

[0162] [Table 11-1]

[0163]

[0164] SC11: free radical polymerizable silane coupling agent synthesized in Synthesis Example 11

[0165] SC12: free radical polymerizable silane coupling agent synthesized in Synthesis Example 12

[0166] SC13: free radical polymerizable silane coupling agent synthesized in Synthesis Example 13

[0167] SC14: free radical polymerizable silane coupling agent synthesized in Synthesis Example 14

[0168] SC15: free radical polymerizable silane coupling agent synthesized in Synthesis Example 15 C-SC11: 3-(trimethoxysilyl)propyl methacrylate C-SC12: 3-(triethoxysilyl)propyl methacrylate C-SC13: free radical polymerizable silane coupling agent synthesized in Comparative Synthesis Example 11 UDMA: di(methacryloyloxyethyl)trimethylhexamethylene diurethane 2G: diethylene glycol dimethacrylate

[0169] Initiator: Diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide

[0170] [Table 11-2]

[0171]

[0172] SC11: free radical polymerizable silane coupling agent synthesized in Synthesis Example 11

[0173] SC12: free radical polymerizable silane coupling agent synthesized in Synthesis Example 12

[0174] SC13: free radical polymerizable silane coupling agent synthesized in Synthesis Example 13

[0175] SC14: free radical polymerizable silane coupling agent synthesized in Synthesis Example 14

[0176] SC15: free radical polymerizable silane coupling agent synthesized in Synthesis Example 15 C-SC11: 3-(trimethoxysilyl)propyl methacrylate C-SC12: 3-(triethoxysilyl)propyl methacrylate C-SC13: free radical polymerizable silane coupling agent synthesized in Comparative Synthesis Example 11 UDMA: di(methacryloyloxyethyl)trimethylhexamethylene diurethane 2G: diethylene glycol dimethacrylate

[0177] Initiator: Diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide

[0178] [Table 12-1]

[0179]

[0180] [Table 12-2]

[0181]

[0182] [Table 12-3]

[0183]

[0184] Evaluation results

[0185] Evaluation Results Table 22-1 shows the results of the bending strength test of the medical and dental composite resins prepared based on the examples. From these results, particularly significant differences were confirmed in the composite resins (Examples 22-1 to 22-5) using monomers (Monomer-B) having benzene rings and cyclohexane rings in the molecular skeleton of the binder resin. That is, the medical and dental composite resins containing microparticles prepared using the silane coupling agent having benzene rings and cyclohexane rings in the basic skeleton synthesized according to the present invention (Synthesis Examples 21 to 25) have significantly higher bending strength characteristics than the medical and dental composite resins using the silane coupling agent used in the past (Comparative Examples 21-1 to 22-1). It can be seen that the fracture energy characteristics are particularly significantly improved. That is, by surface treating the inorganic filler with the silane coupling agent of the present invention, the medical and dental composite resin cured body exhibits toughness, and as a result, a higher mechanical strength is given to the medical and dental composite resin. It is speculated that this is the result of the addition of multiple carbamate groups in conjunction with the introduction of benzene rings and / or cyclohexane rings into the basic skeleton of the silane coupling agent. The above evaluation results (bending strength test results) show that the silane coupling agent of the present invention having a benzene ring, a cyclohexane ring, and two carbamate groups can be applied to and provided in general industries such as medical and dental curable compositions having higher mechanical strength than that achieved by the prior art, bonding to electronic component material substrates including smartphones, bonding to automotive raw materials, etc.

[0186] Next, the measurement results of the Hazen color number obtained in the color stability test are shown in Table 22-2. These measurement results show that the Hazen color number of the polymerizable silane coupling agent not containing a platinum complex synthesized in Synthesis Examples 21 to 25 did not show a large difference just after synthesis and after being stored in the dark at 50°C for 1 month. In contrast, the Hazen color number of the polymerizable silane coupling agent containing a platinum complex synthesized in Comparative Synthesis Example 11 showed a large difference just after synthesis and after being stored in the dark at 50°C for 1 month. It is believed that this large color change originates from the residual platinum complex.

[0187] Next, the measurement results of the color tone stability of the cured product are shown in Table 22-3. These measurement results show that no significant difference in the change of color tone was observed in the cured medical and dental composite resin containing the inorganic filler surface-modified using the polymerizable silane coupling agent containing no platinum complex synthesized in Synthesis Examples 21 to 25. In contrast, the cured medical and dental composite resin containing the inorganic filler surface-modified using the polymerizable silane coupling agent containing a platinum complex synthesized in Comparative Synthesis Example 1 had a significant difference in the change of color tone, and yellowing was significant.

[0188] These test results show that the discoloration caused by the important precious metals that cannot be confirmed aesthetically in the medical dental curable composition is epoch-making. In addition, the precious metals as hydrosilylation catalysts are not used at all during synthesis, so that the reduction of manufacturing costs becomes possible. And then, by using a compound with isocyanate groups at both ends as a reaction matrix, the reagent solubility of organic solvents is significantly improved during synthesis, so that, compared with 1-10-decanediol, carbamate reaction can be carried out at a high temperature. This is also related to the shortening of the reaction time, which becomes the result related to the reduction of manufacturing costs.

[0189] [Table 21-1]

[0190]

[0191] SC21: free radical polymerizable silane coupling agent synthesized in Synthesis Example 21

[0192] SC22: free radical polymerizable silane coupling agent synthesized in Synthesis Example 22

[0193] SC23: free radical polymerizable silane coupling agent synthesized in Synthesis Example 23

[0194] SC24: free radical polymerizable silane coupling agent synthesized in Synthesis Example 24

[0195] SC25: free radical polymerizable silane coupling agent synthesized in Synthesis Example 25

[0196] SC11: free radical polymerizable silane coupling agent synthesized in Synthesis Example 11

[0197] SC12: the free radical polymerizable silane coupling agent synthesized in Synthesis Example 12 C-SC13: the free radical polymerizable silane coupling agent synthesized in Comparative Synthesis Example 11 Monomer-A: 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane

[0198] -1,16-diylbis(2-methacrylate)

[0199] Monomer-C: Oxybis(ethane-2,1-diyl)bis(2-methylacrylate) Initiator: Diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide

[0200] [Table 21-2]

[0201]

[0202] SC21: free radical polymerizable silane coupling agent synthesized in Synthesis Example 21

[0203] SC22: free radical polymerizable silane coupling agent synthesized in Synthesis Example 22

[0204] SC23: free radical polymerizable silane coupling agent synthesized in Synthesis Example 23

[0205] SC24: free radical polymerizable silane coupling agent synthesized in Synthesis Example 24

[0206] SC25: free radical polymerizable silane coupling agent synthesized in Synthesis Example 25

[0207] SC11: free radical polymerizable silane coupling agent synthesized in Synthesis Example 11

[0208] SC12: free radical polymerizable silane coupling agent synthesized in Synthesis Example 12

[0209] C-SC13: Free radical polymerizable silane coupling agent synthesized in Comparative Synthesis Example 11

[0210] Monomer-B: ((((methylenebis(4,1-phenylene))bis(azanediyl))bis(carbonyl))bis(oxygen))

[0211] Bis(ethane-2,1-diyl)bis(2-methacrylate)

[0212] Monomer-C: Oxybis(ethane-2,1-diyl)bis(2-methacrylate)

[0213] Initiator: Diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide

[0214] [Table 22-1]

[0215]

[0216] [Table 22-2]

[0217]

[0218] [Table 22-3]

[0219]

[0220] Industrial Applicability

[0221] The silane coupling agents currently used are not limited to the medical and dental fields and the general industrial fields, and are generally low-molecular 3-(trimethoxysilyl)propyl methacrylate, etc. In addition, in order to further improve various physical properties, silane coupling agents with long alkylene chains are used. However, compared with low-molecular silane coupling agents (alkylene chain number: 3, etc.), although the silane coupling agents with long alkylene chains have the effect of improving various physical properties, they need to use a hydrosilylation reaction with a noble metal catalyst during synthesis, and therefore, they are significantly inferior in terms of discoloration, etc. The silane coupling agent of the present invention completely overcomes these problems.

[0222] Furthermore, using diisocyanates (preferably diisocyanates having benzene rings and / or cyclohexane rings) as good solvents such as toluene as reaction substrates, the organic solvents that can be selected are increased compared to organic solvent poorly soluble compounds such as 1-10-decanediol. That is, even when a higher temperature can be selected in the carbamate reaction, in order to reduce manufacturing costs, etc., and then for free radical polymerizable group monomers having benzene rings and / or cyclohexane rings, there is high affinity, etc., therefore, it can be said that the industrial availability is large.

Claims

1. A silane coupling agent having a polymerizable group, wherein the silane coupling agent is represented by any one of the following formulae:

2. The silane coupling agent according to claim 1, wherein The silane coupling agent is represented by any of the following formulas:

3. The silane coupling agent according to claim 1, wherein The silane coupling agent is represented by any of the following formulas:

4. The silane coupling agent according to claim 1, wherein The silane coupling agent is represented by any of the following formulas:

5. The silane coupling agent according to claim 1, wherein The silane coupling agent is represented by any of the following formulas:

6. The silane coupling agent according to claim 1, wherein The silane coupling agent is represented by any of the following formulas:

7. The silane coupling agent according to claim 1, wherein The silane coupling agent is represented by any of the following formulas: 8 . An inorganic filler surface-treated with the silane coupling agent according to claim 1 . 9 . A curable composition for medical and dental use, comprising the inorganic filler according to claim 8 , a radical polymerizable monomer, and at least one of a polymerization initiator and a polymerization accelerator. 10 . The medical and dental curable composition according to claim 9 , wherein the radical polymerizable monomer has at least one of a benzene ring and a cyclohexane ring in its molecular skeleton.